Investigating the Role of Space Factors in Promoting Vitality for Designing Sports Complex - Amir Reza Karimi Azeri; Mehraneh Aladini; Mehrdad Amirnezhad Mozhdehi (Civil Engineering Journal, 2018)
The quality of urban public space has been one of the focal points of recent design research, with the efforts to create such a public space that could satisfy citizens in different terms has been proposed as one of the main strategies for the urban design projects. As one of the factors affecting the quality of public spaces and urban environments, vitality plays an important role in such settings. On the other hand, the environmental designers are always faced with different aspects of designing public spaces and the important fact is that, among the various factors influencing the vitality, which one has the most important role. In this regard, this study intends to focus on the designing of sports complex in Bandar Anzali in order to enhance the vitality. In terms of research kind, the research is a descriptive-analytical one, in terms of methodology, it uses a survey method and it is functional based on objective. According to the data, it is a quantitative research and it is a field study in terms of implementation. In this regard, among the human-based and environmental variables related to the vitality that were extracted from the documentary and desk research, five cases were selected  as the basis of the research according to the prioritization of environmental psychology developed by the  experts from the faculty of members from the prestigious Iranian  universities. Additionally, the research tools were developed based on this prioritization. The statistical community of the present study involved two cases of the sports complexes representing Bandar Anzali. Therefore, with the determination of the community, sample size and research tools, the selected variables were tested to accept or reject the hypotheses. After analyzing the data by SPSS software, visual beauty, security, sociability, readability and user interaction and 24 hour activity were prioritized respectively. As a result, the analytical model of the research, which in fact includes the main factors affecting the vitality of sports spaces has been formulated as a public space in Anzali.  Finally, the most effective spatial strategies have been presented to promote vitality and to achieve the research goals.